ERDOSTEINE SALVAGES CARDIAC NECROSIS: NOVEL EFFECT THROUGH MODULATION OF MAPK AND NRF-2/HO-1 PATHWAY. (April 2021) - Mutneja, Ekta; Verma, Vipin; Malik, Salma; Arya, D.S.
Abstract : Objective: To assess the pharmacological and molecular effects of erdosteine in ISO induced myocardial necrosis in rats Design and method: To optimize the effect of erdosteine against experimental model of myocardial necrosis, male albino Wistar rats were divided into eight groups (n = 6) i.e. normal, ISO-control (ISO-C), erdosteine treatment with ISO. Rats in treatment groups were administered erdosteine orally for 28 days, whereas in normal and ISO-C group, 1% CMC was administered orally at 2 ml/kg/day for 28 days. Two consecutive doses of ISO 85 mg/kg, s.c. were given to ISO-C and erdosteine treatment groups on 27th and 28th day at 24 h interval. On 29th day, hemodynamic parameters were recorded and animals were sacrificed to excise their heart for measurement of various parameters. Results: In ISO-C rats, significantly increased levels of inflammatory markers, pro-oxidants and structural damage was observed as compared to normal group. Furthermore, immunohistochemistry revealed an increased expression of apoptotic proteins and decreased expression of anti-apoptotic protein which was further confirmed through TUNEL assay. Pretreatment with erdosteine at 80 mg/kg and 160 mg/kg reversed the deleterious effects of isoproterenol and normalized myocardial architecture. Erdosteine showed anti-inflammatory and anti-apoptotic activities through inhibition of MAPK pathway. Furthermore, erdosteine partially activated transcription factor Nrf-2 and HO-1 expressions showing the anti-oxidant potential of erdosteine. Conclusions: Thus, this study revealed the new use of an old drug and concluded the protective effect of erdosteine in ISO-induced myocardial necrosis through combined effect of MAPK and Nrf-2/HO-1 pathway.